Investigation on Malondialdehyde, S100B, and Advanced Oxidation Protein Product Levels in Significant Hyperbilirubinemia and the Effect of Intensive Phototherapy on these Parameters - Dilek Sarici; Tamer Gunes; Cevat Yazici; Mustafa Ali Akin; Levent Korkmaz; Seyma Memur; Selim Kurtoglu; Mehmet Adnan Ozturk; Serdar Umit Sarici (Pediatrics and Neonatology)
The parameters of oxidative stress [advanced oxidation protein products (AOPPs), malondialdehyde (MDA), and S100B] and the effect of intensive phototherapy (PT) on these parameters have not been studied extensively in newborns with significant hyperbilirubinemia (SH). We aimed to measure the levels of MDA, S100B, and AOPPs in newborns with SH, and to compare newborns with healthy control newborns without hyperbilirubinemia on the basis of these parameters of oxidative stress. In addition, we investigated the effect of intensive PT on these parameters during the treatment of SH and report our findings for the first time in the literature. Methods: The study was performed in newborns (n = 62) who underwent intensive PT because of SH. Newborns without jaundice constituted the control group (n = 30). Both groups were compared with respect to demographic characteristics and biochemical (laboratory) parameters including MDA, AOPPs, and S100B. MDA, AOPPs, and S100B were also compared before and after intensive PT in the PT group. In the study group, a correlation analysis of demographic characteristics; MDA, AOPP, and S100B values; and changes occurring in MDA, AOPPs, and S100B values due to the effect of intensive PT was performed. Results: Serum total bilirubin, S100B, and MDA levels in the PT group before performing PT were significantly higher than those in the control group. In newborns receiving PT serum total bilirubin, MDA and AOPP levels decreased significantly after intensive PT. In correlation analysis, a statistically significant negative correlation was found only between the amount of bilirubin decrease with PT and AOPP levels after PT in the study group. Conclusion: Whether the significant decrease in MDA levels, which was higher prior to PT, is due to the decrease in serum bilirubin levels or due to the effect of intensive PT itself remains to be determined in further studies. The decrease in AOPP levels after PT implies that intensive PT has protective effects on oxidative stress.